Ameliorating Effect of Olive Leaf Extract on Cyclosporine-induced Nephrotoxicity in Rats (Iranian Journal of Kidney Diseases, 2015)
Introduction. Olive leaves are traditionally used in the Mediterranean basin in many medical conditions for its potent antioxidant activity. Cyclosporine A, a well-known immunosuppressant, can induce nephrotoxicity through oxidative stress. This study investigated the effect of olive leaf extract (OLE) on cyclosporine-induced nephrotoxicity in rats. Materials and Methods. Thirty Wistar rats (180 g to 200 g) were classified into 5 groups, each containing 6 rats. The first group received normal saline and served as control. The second group was treated with cyclosporine, 25 mg/kg for 21 days for nephrotoxicity induction. Groups 3 to 5 were treated with cyclosporine, 25 mg/kg in addition to different doses of OLE (40 mg/kg, 80 mg/kg, and 120 mg/kg), respectively, for 21 days. After 21 days, the rats' body weights were recorded and the rats were sacrificed. Blood samples were collected and the animals were necropsied. Both kidneys were removed, one for histopathological and one for antioxidant activity evaluations. Results. Cyclosporine significantly reduced body weight and kidney weight; serum total protein, albumin, and sodium levels; and renal glutathione peroxidase, catalase, and superoxide dismutase. It also increased serum urea, creatinine, and calcium levels as compared to the control group. Groups 4 and 5 showed a significantly greater body weight and kidney weight; higher serum sodium, total protein, and albumin levels; greater glutathione peroxidase, catalase, and superoxide dismutase; and lower serum urea, creatinine, and calcium levels as compared to group 2. Conclusions. Treatment with OLE can alleviate cyclosporine-induced nephrotoxicity when used in a proper dose.